Checklist of the earthworm fauna of Croatia (Oligochaeta: Lumbricidae) - Kutuzović, Davorka Hackenberger; Kutuzović, Branimir Hackenberger (Zootaxa, 2013)
A checklist of the Croatian earthworm fauna (Oligochaeta: Lumbricidae) is presented, including published records and authors’ personal data. This is the first checklist for Croatia only, with comprehensive information for each earthworm species regarding ecological category, habitat, distribution type and distribution in Croatia. The currently known earthworm fauna of Croatia comprises 68 species belonging to 17 genera, with Octodrilus being the species-richest genus (15 species). Chorologically these species can be allocated to 13 different types of distribution. Nineteen species are endemic of which 10 species are endemic to Croatia and 9 species are endemic to Croatia and neighbouring countries (Italy, Slovenia, Hungary, and Montenegro). The endemic earthworms are distributed in the areas of higher altitudes in the Continental and Alpine biogeographic region, mostly covered with forest or autochtonous vegetation.